MEBAUAC: Methodology for elaborating a baseline of the accomplishment of university accreditation criteria - Alfaro Paredes, Emigdio Antonio (2020)
The purpose of the study was to propose and apply a quick methodology for elaborating a baseline of the accomplishment of university accreditation criteria in university careers, with the perception of the professors and academic authorities and to apply it to a city. MEBAUAC is original and has permitted the establishment of a baseline. There were not found previous similar methodologies. The instrument of the evaluation is original too, and was applied to the evaluation of the accomplishment of university accreditation criteria of engineering careers with a sample of 73 professors and academic authorities of engineering careers in the city of Lima, capital of Peru. Using the proposed methodology, there were results of the accomplishment of the following criteria: (a) the knowledge of the adequate strategies of teaching-learning processes by professors, (b) the implementation of welfare programs (library, arts, health attention, recreational activities, etc.), (c) long term planning, (d) elaboration of adequate study planning according to the requirements of the labor market, (e) application of adequate strategies for teaching-learning processes, (f) tutorship, (g) university extension and social projection, (h) spaces and equipment, and (i) relationships with interest groups. Future researches about the evaluation of the accreditation process must take into account the focuses for university schools, for government authorities, and for interested researchers.